Impactos da adoção da INTERNET na hotelaria : a percepção dos gerentes de hotéis de médio e grande porte de Natal / RN - Mendes Filho, Luiz Augusto Machado (2006)
The hotel industry is increasingly using the Internet like a management and operational tool. That way, the hotels will be more prepared to offer quality services to their guests and increase their profits as well. However, many managers seem don t perceive the advantages brought from this new digital environment. This thesis analyse the effects of the hotel managers perceptions as for the Internet effectiveness, Internet access, Internet as a communication tool, future importance of the Internet, benefits and drawbacks of the Internet, according to property type (simple, medium comfort and luxe), property size (quantity of the apartaments), age and hotel industry experience of the managers. The methodology utilized was a survey about the hotels that had at least 40 apartments (medium and big property size), were working in Natal-RN and classified in categories in the Guia Quatro Rodas Brasil, totalizing 35 hotels. Through the analysis of variance (ANOVA) and Tukey test, the results showed that the hotel managers with more than 50 apartments, the managers of the hotel more comfortable, the younger managers and the managers less experient in the hotel industry, demonstrated more conscious about the importance of the adoption of the Internet than the rest of the others. The contribution of this work is to offer more knowledge to the hotel executives about how they can use the Internet and show the importance of the web adoption in their properties